Lifestyle wellness coaching James Gavin, Madeleine Mcbrearty - Gavin, James 1942-; Mcbrearty, Madeleine 1948- (Human Kinetics, 2013)
Helps you learn how to work with individuals looking to tackle such issues as weight management, nutritional balance, exercise regularity, stress management and sleep issues with a focus on a balanced, complete wellness approach. This title employs an approach which allows individuals flexibility on how they use the book